Association between daily screen time and risk of stroke among middle-aged and elderly people: research based on China health and nutrition survey - Ren, Yaxin; Sun, Kejuan; Rong, Yueqing; Song, Shiming; Zhai, Yijing; Miao, Junjie; Shi, Hongmei; Xue, Hongmei; Li, Zengning (Frontiers in Sports and Active Living, 2023)
We aimed to explore the independent associations of screen time and the risk of stroke among Chinese adults based on the China Health and Nutrition Survey (CHNS). Methods: Data on Chinese adults aged > 40 years from CHNS in 2004-2009 were selected. 4587 individuals were included in 2009, including screen time and the risk of stroke. Simultaneously, we traced the previous screen time to 2004 for those with outcome measures in 2009 (n=2100). Basic information, lifestyle and screen behavior were obtained through face-to-face interviews and self-completed questionnaire. Anthropometric data collected included blood pressure, body weight, height, hip circumference, waist circumference. Fasting blood was obtained for measurements of lipid and glucose levels. Cross sectional analysis and cohort analysis were both performed using multivariate logistic regression. Results: Of all participants, 3004 (65.49%) participants spent more than 2 hours per day on screen time. Taking the men who spent less than 2 hours on screen per day as reference, the crude OR of the high risk of stroke was 1.53 (95% CI = 1.20-1.95) for the men who spent 2-3 hours per day on screen and 2.37 (95% CI = 1.78-3.16) for the men who spent more than 3 hours per day on screen. This difference remained significant after adjusting for confounding factors. No association was observed among women. However, in the cohort analysis with screen time in 2006 as the independent variable, the association between screen time and stroke risk was found both in men (OR, 1.83 [95% CI,) and women (OR, 1.48 [95% CI, 1.10-1.99)]). Conclusion: We found that the high screen time was associated with an increased stroke risk, which was pronounced in men, warranting a universal need to limit screen time in order to improve health.